(untitled) (Research, Society and Development, 2022)
Objective: To carry out a parasitological survey of molluscs in São Cristóvão/Sergipe. Methods: This is a descriptive and investigative study carried out in the city of São Cristóvão. For this purpose, Molluscs were collected with the aid of metallic tweezers and a perforated metal shell, placed in plastic bags and sent to the Laboratory of Entomology and Tropical Parasitology (LEPaT) of the Federal University of Sergipe (UFS) for identification of the species and the parasitism. Results: A total of 1,669 snails were collected, of which 1605 belonged to the genus Biomphalariae, the others were Physa sp., Pomacea sp., Lymnea sp. and Melanoid sp. Conclusion: The presence of molluscs of the Biomphalariae genus makes it necessary to make the maintenance and life of schistosomiasis (water belly) viable, it is still closely linked to poor socioeconomic indicators, whose primary factors for prevention are health education and sanitation inherent to mollusc control. Therefore, prophylactic actions and working health education with the population are essential to improve their habits and quality of life.